Peningkatan Kemampuan Pemahaman Kosakata Menggunakan Media Wordwall Pada Peserta Didik Tunarungu Di Kelas V SLB Negeri 1 Kota Jambi - Kusumawardani, Fitriana; Mahdi, Arisul (Jurnal Penelitian Pendidikan Khusus, 2024)
The research was motivated by a problem that the author found at SLB Negeri 1 Jambi City. The author found a fifth grade deaf student who had problems understanding the vocabulary of objects, namely that the child was not yet able to write the names of objects. Therefore, the author wants to help students improve their ability to understand object vocabulary by using wordwall media. The research method used is the experimental method. This research uses single subject research with an A-B-A reservation design. This research aims to improve the ability to understand vocabulary using wordwall media for deaf students at SLB Negeri 1 Jambi City. The research subject in this study was a student at SLB Negeri 1 Jambi City in the category of mentally retarded child and female, aged 12 years, class V/B. The data analysis technique used is visual graphic analysis. Measurements are carried out using a percentage of the number of instrument items. Based on the results of this research, it can be concluded that wordwall media is able to improve the ability to understand object vocabulary in class V deaf students at SLB Negeri 1 Jambi City.